2019
DOI: 10.1111/ibi.12732
|View full text |Cite
|
Sign up to set email alerts
|

Urban exploiters have broader dietary niches than urban avoiders

Abstract: Urbanization is currently one of the most pervasive threats to biodiversity worldwide, yet traits permitting birds to exploit urban environments are not fully understood. I used bird traits related to diet (dietary item and foraging stratum), accounting for latitude, body size, development mode and phylogeny, to compare diet breadths of urban exploiters and urban avoiders, using a global dataset (463 bird species). Urban exploiters (urban species) were larger, consumed more vertebrates and carrion, and fed mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 55 publications
1
65
1
2
Order By: Relevance
“…that insectivores are at particular risk from urbanization; Chace and Walsh ) but they often fail to account for the complicated measures of niche specialization (Morelli et al ). Indeed, future work should continue to elucidate specific life history traits which predict a species’ risk to urban ecosystems (Kark et al , Fuller et al , Evans et al a, Guetté et al , Palacio ). Importantly, our analysis highlights a broad general ecological pattern: the degree of overall species’ specialization is negatively correlated with urban tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…that insectivores are at particular risk from urbanization; Chace and Walsh ) but they often fail to account for the complicated measures of niche specialization (Morelli et al ). Indeed, future work should continue to elucidate specific life history traits which predict a species’ risk to urban ecosystems (Kark et al , Fuller et al , Evans et al a, Guetté et al , Palacio ). Importantly, our analysis highlights a broad general ecological pattern: the degree of overall species’ specialization is negatively correlated with urban tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that the strong fragmentation of urban green areas causes changes in the spatial behavior of urban coachwhip snakes Masticophis flagellum (Mitrovich et al 2009), bobcats (Tigas et al 2002) or coyotes (Atwood and Weeks 2003). Changes in the preferences of nesting places, new food sources, and the impact of a new group of urban predators have been widely studied for many species of vertebrates, including reptiles, birds and mammals as well (Contesse et al 2004;Møller 2012;Chavez-Zichinelli et al 2013;Thomas et al 2018; Aviles-Rodriguez and Kolbe 2019; Gallo et al 2019;Palacio 2020). For urban birds, the impact of light and noise pollution on the behavior has also been shown (Moiron et al 2015;Swaddle et al 2015;Weaver et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…While we did record markedly larger TNW in urban than in natural habitats, differences in WIC were negligible and species only showed a non-significant tendency to have larger BIC between these two habitat types. Many studies using different approaches have reported similar patterns of niche expansion across habitat transformation gradients (Bonier et al, 2007;Devictor et al, 2008a;Callaghan et al, 2019;Pagani-Núñez et al, 2019;Palacio, 2019), yet no study had thoroughly addressed how this pattern is a result of changes in different niche characteristics at the individual level. Our study is original in showing this pattern of trophic specialization within species, while previous Results from a set of linear mixed-effects models using the Within-Individual (WIC) and Between-Individual (BIC) niche components, and Individual Specialization (IS = WIC/TNW) in 21 populations of birds and frogs as response variables.…”
Section: Differences In Niche Characteristics Across Habitat Typesmentioning
confidence: 99%
“…This loss is not neutral in that predominantly specialized species -those requiring particular habitat or food resources -are disproportionately lost, while environmental generalists -those with less selective habitat or dietary needs -become dominant (Flynn et al, 2009;Ducatez et al, 2018;Sol et al, 2020). A consequence of this process is that species in transformed habitats display broader niches than species in natural habitats (Bonier et al, 2007;Clavel et al, 2011;Coogan et al, 2018;Pagani-Núñez et al, 2019;Palacio, 2019). It is unclear however how this process of population niche expansion translates into the niches of the individual organisms.…”
Section: Introductionmentioning
confidence: 99%